Effectiveness of Science Textbook Activities for Conceptual Understanding of Students - Sidra Shahid; Dr. Wajiha Kanwal; Khalida Parveen (Journal of Management Practices, Humanities and Social Sciences, 2023)
This research is attempt to check the effectiveness of science textbooks activities for conceptual understanding of learning. The main objective of the study was to develop the conceptual knowledge about science in students. For this purpose, use textbooks activities and different instructional aids for enhancing the conceptual understanding of learners. This study was quantitative in nature. Quasi Experimental research was used to check the effectiveness of use of textbook activities for conceptual understanding of learner at elementary level, which were measured through pre and post-test. An action research was conducted in a public sector, high school in Rawalpindi. Students of grade five were selected to conduct a study. Intervention was carried out throughout whole weak. Pre-test and post-test were taken to collect data and analyzed, by using mean and t-test. The study found a significant difference between teaching of science through traditional method and using textbooks activities as well as other additional instructional aids. In post-test students perform very well as compared in pre-test. It was concluded that intervention has positive effects on students learning performance. This study act as model and guideline for science teachers at elementary level to make their teaching effective and long-lasting during science lesson. This will contribute to better science teaching in schools.